Corruption typology: a review of literature - Suleiman, Naziru; Othman, Zaleha (David Publishing, 2017)
Corruption is increasingly becoming a global phenomenon virtually affecting every part of the world. The effects have been very devastating particularly in the developing nations, by which to a large extent public service functions thrive in an environment heavily characterized by corruption. This paper reviews the relevant and related literature on corruption and then proposes a classification of the type of corruption based on the review